THE RORSCHACH PSYCHODIAGNOSTIC AS APPLIED TO DEAF MUTES - ALTABLE, JOSE PEINADO (Universidad Nacional Autónoma México, Departamento de Física, CD MEXICO, DF, MEX, 1970)
Rorschach responses were obtained from 45 deaf-mute children through the use of "mimic language" with an experienced teacher as interpreter Structural analysis of results revealed as outstanding characteristics of the group: color and shading shock; feel
RORSCH RES EXCH
Keywords: RORSCHACH, PSYCHODIAGNOSTIC, APPLIED, MUTES; MULTIDISCIPLINARIA; PSIQUIATRIA; PSICODIAGNOSTICO